Antifungal iridoids from the stems of Tocoyena formosa - Bolzani, Vanderlan da Silva [UNESP]; Trevisan, LMV; Izumisawa, C. M.; Young, MCM (Soc Brasileira Quimica, 1996)
A new antifungal iridoid compound, together with three active known iridoids, galioside, galioside aglucone, and apodanthoside, as well as 3-O-beta-D-glucopyranosyl-28-O-beta-D-glucopyranosyl quinovic acid and quercetin-3-O-methyl-3-O-beta-D-rhamnopyranoside, were isolated from the stems of Tocoyena formosa. This new compound was characterized by spectral data as 11-O-trans-feruloylteucrein.
Keywords: Tocoyena formosa; Rubiaceae; triterpene saponin; flavonol glycoside; antifungal iridoids